2010
DOI: 10.1007/s12665-010-0666-4
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater depletion and quality deterioration due to environmental impacts in Maheshwaram watershed of R.R. district, AP (India)

Abstract: Maheshwaram watershed is situated in Ranga

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…This observation suggested that the solubility of fluorite and calcite controls the groundwater compositions of components such as F, Ca and carbonate. In line with our results, previous studies have noted that natural groundwater containing elevated F concentrations are often in equilibrium with calcite (Purushotham et al, 2011;Rao, 2011). The equilibrium relationship between F and Ca is constrained by fluorite (CaF 2 ) as shown in Eq.…”
Section: Correlation Between F and Geochemical Parameterssupporting
confidence: 93%
See 2 more Smart Citations
“…This observation suggested that the solubility of fluorite and calcite controls the groundwater compositions of components such as F, Ca and carbonate. In line with our results, previous studies have noted that natural groundwater containing elevated F concentrations are often in equilibrium with calcite (Purushotham et al, 2011;Rao, 2011). The equilibrium relationship between F and Ca is constrained by fluorite (CaF 2 ) as shown in Eq.…”
Section: Correlation Between F and Geochemical Parameterssupporting
confidence: 93%
“…PCS1, which explained 34.5% of the total variance, was mainly influenced by Na, HCO 3 , TDS, SO 4 , pH, Cl, Ca, and F. This component represented major cations and anions resulting from the mineral weathering and water-rock interactions in the aquifer (Purushotham et al, 2011). Therefore, this natural process plays a significant role in the occurrence of F in Shanxi.…”
Section: Principal Component Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…Takem et al (2010) carried out groundwater study from springs and bore wells in a alluvial aquifer and conclude that the area is contaminated with nitrate pollution due to anthropogenic activities. Purushotham et al (2011) has carried out similar studies of groundwater and conclude that the groundwater deteriorated due to rapid urbanization. Suyash and Pawar (2011) has carried out accentuation of heavy metals in groundwater and its spatio-temporal variation through using GIS techniques in Ankaleshwar industrial estate, India and conclude that the GIS techniques have facilitated the monitoring of spatio-temporal behaviors of heavy metals and site-specific accretion pattern using raster and color composite maps of shallow groundwater system.…”
Section: Introductionmentioning
confidence: 96%
“…The major ions (i.e., Cl, Na, K, and Mg) are associated with hydrochemical variables from mineral weathering and water-rock interactions in the aquifer, which indicates that F1 would reflect climatic and geological (lithological) effects. Other studies also showed that major ions reflected effects of geothermal system and mineral weathering (Al-Farraj et al, 2013;Brahman et al, 2013;Chapagain et al, 2010;Purushotham et al, 2011). However, the water quality variables, like HCO 3 and NH 4 -N, are closely related to organic matter contents in the aquifers (Jia et al, 2014;Oremland and Stolz, 2005).…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 98%